Bacterial colonization associated with fixed orthodontic appliances. A scanning electron microscopy study - Sukontapatipark, Warat; El‐Agroudi, Mohammad A.; Selliseth, Nils J.; Thunold, Kirsten; Selvig, Knut A. (European journal of orthodontics, 2001)
This investigation was undertaken to assess bacterial plaque accumulation adjacent to orthodontic brackets. Experiments were carried out on 11 subjects who were scheduled for orthodontic treatment including extraction of two or four premolars. Metal brackets were bonded to the premolars to be extracted using macro‐filled bonding composite. A conventional elastomeric ring was placed around one bracket and a steel ligature wire around the bracket on the contralateral tooth. The subjects were told to continue their normal oral hygiene regimen. Teeth were extracted at 1, 2, or 3 weeks after bracket bonding. Scanning electron microscopic (SEM) examination of brackets, excess composite, and buccal enamel revealed that mature plaque was present on excess composite at 2 and 3 weeks after bonding, whereas plaque on the gingival enamel surface was still at an early stage of development. The results demonstrate that excess composite around the bracket base is the critical site for plaque accumulation due to its rough surface and the presence of a distinct gap at the composite–enamel interface. The method of ligation does not appear to influence the bacterial morphotypes on both composite and enamel surfaces.